Gendering Environment and Climate Change in the Economic Community of West African States & the East African Community: Why Representation Matters. Issue 2 (June 2022) - Sackeyfio, Naaborle; Kaba, Amadu Jacky
The heightened prospect of a "rising Africa" stems from multiple developments across the continent. Technological innovation, economic empowerment, increasing female leadership, and more continue to raise the fortunes of African countries. As regional economic communities engage with Agenda 2063, an ambitious endeavor to support and sustain economic development, a gendering environment is pivotal to any ensuing progress. Using the case studies of two regional organizations, our research examines the pace of political representation of women in relevant environmental committees in the Economic Community of West African States and the East African Community. In an epoch where women constitute half of the continent, the case for female representation to combat ecological challenges propelled by the securitization of environmental issues is paramount.